Pengaruh Media Pembelajaran Quizizz Berbasis Game Edukasi Terhadap Hasil Belajar Siswa dalam Mata Pelajaran Seni Budaya Kelas VII MTs PUI Ciawigebang - Nurpadilah, M. Ipad; Mahpudin, Asep (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to determine the influence of the use of educational game based Quizizz learning media on student learning outcomes in the subject of Cultural Arts in grade VII MTs PUI Ciawigebang. The research method used is an experiment with a research design, namely a nonequivalent control group design. The research sample consisted of two classes, namely an experimental class consisting of 30 students using Quizizz learning media and a control class consisting of 30 students using conventional methods. The test statistics used for hypothesis testing are the Paired Sample T-Test. The results of data analysis showed that the average score of the pretest of the experimental class was 48.67 and the posttestwas 83.50, while the results of the control class pretest obtained a score of 53.67 and the posttest75.00. Based on data analysis, it can be concluded that there is a significant increase in student learning outcomes in the experimental class compared to the control class. Based on the results of the study, it was shown that there was an influence of the use of Quizizz learning media on the learning outcomes of grade VII students in the subject of Arts and Culture